O desenho como ferramenta do projeto de design de joias - LLABERIA, Engracia Maria Loureiro da Costa (2016)
This thesis presented to the PhD Program of Design at Anhembi Morumbi University, deals with the importance of drawing as a tool for jewelry design, considering its typology applied to different stages of development process, from creation to production, in the jeweler sector, devoting special attention to the industrial segment. This study analyzes the different activities related to the creation of the jewel, such as the High Jewelry and the Contemporary Jewelry, in relation to the use of drawing in different moments. Searching for basis in the drawings of Architecture as reference to studies of forms, volumes and spatial vision development, in the transposition of mental images of three-dimensional objects to the two-dimensional representation. It presents the works of designers and jewelers/artists through interviews and visits to their ateliers as a way of illustrating, also with their drawings, the relevance of this technique representing their ideas. Those professionals were selected for the relevance of theirs works and the attention dedicated to the form research through drawing, since roughs and sketches. Their production and reports are inserted through the chapters, to clarify the approach of each subject. It aims, therefore, to enhance and encourage the teaching of drawing in the training of design professionals and others who dedicate themselves to the production of jewelry in Brazil.